Thrombolysis for acute ischaemic stroke: consumer involvement in design of new randomised controlled trial - Koops, Liedeke (BMJ, 2002)
OBJECTIVES: To determine whether consumer involvement would help to solve some of the ethical problems associated with research into thrombolysis for acute ischaemic stroke, with its inherent risk of fatal intracranial haemorrhage. DESIGN: Quantitative and qualitative research. SETTING AND PARTICIPANTS: Consultation phase: three meetings were held to discuss the planned research, and participants completed a questionnaire. Qualitative work: focus group meetings explored the issues raised during the consultation phase. Design of information leaflets for patients and relatives: trial materials were drafted during the consultation phase and revised in the light of feedback from the focus group meetings and review by patients and carers on a stroke rehabilitation unit. RESULTS: 54 people attended the consultation meetings. Four (9%) participants considered the risks of thrombolysis too great, but most (89%) were prepared to accept the treatment in a clinical trial. Nearly all would accept treatment if it was shown to be effective. Most (85%) would give their consent to enter the planned trial. The focus group meetings and feedback from patients and carers led to significant changes in the information leaflets. The revised trial materials were considered ethical by a national multicentre research ethics committee. CONCLUSIONS: Consumers generally supported a planned trial, and their involvement helped to refine trial consent procedures and led to an ethically acceptable trial design.